STAGIA Â€“ INTERNSHIP PLATFORM FOR THE EVANGELICAL UNIVERSITY OF GOIS (CIPEEX, 2022)
ANALYZING THE ACTUAL SITUATION OF UNIEVANGLICA INTERNSHIPS, IT€™S POSSIBLE TO SEE THE LACK OF STANDARD AND CENTRALIZATION OF HIS MANAGEMENT. EACH ONE OF THE TEACHERS HAS HIS OWN WAY TO MANAGE THIS DOCUMENTATION, CAUSING THE LACK OF INTEGRITY AND SECURITY OF THESE DOCUMENTS. THIS WORK PROPOSES TO REALIZE THE DEVELOPMENT OF A FEATURE NAMED STAGIA, THAT CAN HELP THE RESPONSIBLE TEACHERS TO MANAGE THE INTERNSHIPS OF THE INSTITUTION, USING TOOLS AND TECHNIQUES NEEDED TO BUILD A QUALITY SOFTWARE PRODUCT. THEREFORE, IT€™S PROPOSED THE IMPLEMENTATION AND PLANNING OF METRICS, METHODOLOGIES AND PRACTICE DEVELOPMENT IN ORDER TO OBTAIN A FUNCTIONAL PRODUCT AT THE END OF PROJECT EXECUTION.
Keywords: Internships; Internship Management; Software; University